2015
DOI: 10.1002/ieam.1701
|View full text |Cite
|
Sign up to set email alerts
|

Active biomonitoring withCorbiculafor USEPA priority pollutant and metal sources in the Anacostia River (DC, Maryland, USA)

Abstract: The freshwater Anacostia River watershed (Maryland, DC, USA) was surveyed for the sources of bioavailable US Environmental Protection Agency (USEPA) Priority Pollutants and toxic metals by active biomontoring (ABM) using the freshwater Asiatic clam Corbicula fluminea. The Anacostia River is a 456 km(2) tributary of the tidal freshwater Potomac River that includes the city of Washington, DC where edible fish are highly contaminated with PCBs and chlordane. From 1999 to 2011, Corbicula were collected for ABM fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The Anacostia watershed is historically known to have measurable concentrations of various legacy chemicals and persistent pollutants, some of which have been identified in PBS [15]. A biomonitoring study with clams placed in PBS showed the accumulation of polyaromatic hydrocarbons (PAHs), metals, pesticides, and polychlorinated biphenyls (PCBs) [21]. These compounds are known to alter fish behavior, growth, and/or survival [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The Anacostia watershed is historically known to have measurable concentrations of various legacy chemicals and persistent pollutants, some of which have been identified in PBS [15]. A biomonitoring study with clams placed in PBS showed the accumulation of polyaromatic hydrocarbons (PAHs), metals, pesticides, and polychlorinated biphenyls (PCBs) [21]. These compounds are known to alter fish behavior, growth, and/or survival [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%